1977
DOI: 10.1073/pnas.74.9.3879
|View full text |Cite
|
Sign up to set email alerts
|

Pure and mixed erythroid colony formation in vitro stimulated by spleen conditioned medium with no detectable erythropoietin.

Abstract: Cells from CBA fetal mouse liver formed pure or mixed erythroid colonies in semisolid agar culture after stimulation by medium conditioned by pokeweed mitogenstimulated mouse spleen cells. In general shape, the erythroid colonies resembled typical 7-day single or multiple (burst) colonies. However one-third to one-hal containe, in addition to erythroid cells, macrophages and neutrophils and, less commonly, megakaryocytes or eosinophils. Culture of micromanipulated single colony-forming cells showed these eryth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(73 citation statements)
references
References 11 publications
0
72
0
1
Order By: Relevance
“…Mouse spleen conditioned medium (MSCM) was prepared by the method of Johnson and Metcal [29) BPA assay for purification. BPA was assayed with a minor modification of the method described by Iscove et al,3D) throughout the purification of BPA.…”
Section: Methodsmentioning
confidence: 99%
“…Mouse spleen conditioned medium (MSCM) was prepared by the method of Johnson and Metcal [29) BPA assay for purification. BPA was assayed with a minor modification of the method described by Iscove et al,3D) throughout the purification of BPA.…”
Section: Methodsmentioning
confidence: 99%
“…Antony Burgess went on with Metcalf to purify GM-CSF to apparent homogeneity from mouse-lungconditioned medium by 1977 (13). In 1976 Burgess invited Nicos Nicola (figure 5) (who had also trained with Syd Leach) to join him and Metcalf in the biochemical characterization of the CSFs.…”
Section: Purification and Cloning Of The Csfsmentioning
confidence: 99%
“…Since semisolid culture assays for murine [17,18] and human [19] multipotential progenitors had been reported, a number of investigators had observed the presence of lymphocytes or precursors of lymphocytes in murine and human multilineage colonies. However, the clonal origin of these colonies was never firmly established in these studies.…”
Section: Two-step Clonal Culture Assay For Murine Lymphohematopoieticmentioning
confidence: 99%